Assessment of completeness and legibility of handwritten prescriptions in six community chain pharmacies of Asmara, Eritrea: a cross-sectional study - Dawit G. Weldemariam; Nebyu Daniel Amaha; Nuru Abdu; Eyasu H. Tesfamariam (BMC, 2020)
Abstract Background Incompleteness and illegibility of prescriptions are prescription errors that account for a high proportion of medication errors that could potentially result in serious adverse effects. Thus, the objective of this study was to assess the completeness and legibility of prescriptions filled in the community chain pharmacies. Methods An analytical and cross-sectional study was conducted in the six government owned community chain pharmacies of Asmara, Eritrea from June 3rd to 10th, 2019 using a stratified random sampling technique. A total of 385 prescriptions were analyzed for completeness and legibility by three pharmacists (two experienced and one intern pharmacist). Descriptive statistics and multinomial logistic regression were employed using IBM SPSS® (Version 22). Results A total of 710 drugs were prescribed from the 385 prescriptions assessed. On average, a prescription was found to have 78.63% overall completeness. In the majority of the prescriptions, patient's information such as name, age, sex, and prescriber's identity were present. Prescribed drugs' information such as dose, frequency and quantity and/or duration were present in 83.7, 87.7, and 95.1% respectively. Moreover, generic names were used in 83.3% of the drugs prescribed. About half (54.3%) of the prescriptions' legibility were classified in grade four (clearly legible) and 30.6% in grade three (moderately legible). It was observed that legibility significantly increased with an increase in percentage completeness (rs = 0.14, p = 0.006). However, as the number of drugs written in brand name increased, legibility decreased (rs = − 0.193, p < 0.001). Similarly, as the number of drugs prescribed increased, legibility decreased (rs = − 0.226, p < 0.006). Conclusion Majority of the handwritten prescriptions received in the community pharmacies of Asmara are complete and clearly legible.